Colombian repertoire for teaching in symphonic direction programs (2010)
The article uses a graphic methodology based on the constructive elements of symphonic works in order to select some compositions from the Colombian repertoire, elaborate a piano four hand reduction to four pieces, and to include them as teaching material for symphonic direction courses in universities throughout the country. In the introduction, the article exposes the total absence of Colombian oeuvres as part of the study plan of music programs, and the reasons for that to happen. The methodology establishes the principles and technical resources proper to the occupation, and the criteria for selecting the compositions. And the results include a selection of twelve works, its educational application from the graphs conceived before, and a fragment of a piano four-hand reduction of one of them as a sample. The text concludes that, owing to the research project to which the article is just a brief résumé, music schools in Colombia now have a number of works by local composers that can be used for teaching in symphonic direction programs.